2018
DOI: 10.1007/s00590-018-2291-y
|View full text |Cite
|
Sign up to set email alerts
|

Sprengel’s deformity of the shoulder joint treated by Woodward operation

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies (441 patients) reported the grade of deformity, according to the Cavendish classification [ 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 35 , 36 , 37 , 41 , 42 , 44 , 45 , 46 , 48 , 52 , 53 , 55 , 58 , 59 , 60 ]. Ninety-seven patients (22%) were grade 4, 283 patients (64.2%) were grade 3, 51 patients (11.5%) were grade 2 and 10 patients (2.3%) were grade 1.…”
Section: Resultsmentioning
confidence: 99%
“…13 The contemporary results of Woodward procedure showed a positive correlation of functional and cosmetic outcomes through short and long terms, with the procedure and more improvement occurs in cases of younger age at the time of surgery. 14 Previous studies furthermore reported the best time for surgery to be between 3 and 8 years of age, whereas Jeannopoulos advocates surgery for children between 2 and 5 years of age. 7,15 At a younger age, the procedure is likely to be too difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, our main objective is to shed light on and emphasize the importance of further investigations with regard to the spinal deformities that can occur in patients suffering from MURCS association. We also wanted to highlight the procedure performed; in the standard Woodward's procedure, the paraspinal musculature such as the trapezius and the rhomboids muscles are sutured to the spinous process more caudally in order to put the scapula in a downward position [11][12][13]. Ahmad, in his study, used a modified Woodward's procedure by anchoring the scapula to the lower dorsal vertebrae by stout suture through the superomedial scapula and achieved better shoulder abduction and correction of glenoid tilt [14].…”
Section: Discussionmentioning
confidence: 99%